Islamisasi Jawa - Azyumardi Azra (Studia Islamika, 2013)
Bookreview: M.C. Ricklefs, Islamisation and Its Opponents in Java: A Political, Social, and Religious History, c. 1930 to the Present (Singapore: NUS Press, 2012, xxi+575 halaman)This work of Ricklefs is the last in a trilogy and follows Mystic Synthesis in Java: A History of Islamisation from the Fourteenth to the Early Nineteenth Centuries (2006), and Polarising Javanese Society: Islamic and Other Visions c. 1830–1930 (2007). The three works comprehensively discuss the Islamization of Java since the 14th century. Observing the process and dynamics of Islamization in Javanese society during the centuries up until the contemporary era, Ricklefs concludes that Javanese Muslims have surpassed the difficult times of the early spread of Islam, the era of Dutch and Japanese colonialism, the messy government of Soekarno, the totalitarian government of Soeharto, and contemporary democratic period. Undergoing various changes, Javanese Muslims have become an outstanding example of increased Islamic religiosity. The three works dispute the assumption of many scholars that a large part of Javanese–Muslim society is abangan, or nominal, Muslim.DOI: 10.15408/sdi.v20i1.352